1998
DOI: 10.1073/pnas.95.9.4959
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that HetR protein is an unusual serine-type protease

Abstract: The hetR gene plays a very important role in cell differentiation of heterocystous cyanobacteria. To understand the mechanism of the hetR gene product in regulation of heterocyst differentiation, the recombinant HetR protein (rHetR) was overproduced in Escherichia coli. Purified rHetR was unstable and degraded easily in solution. Phenylmethanesulfonyl f luoride, a serine-type protease inhibitor, prevented the degradation and was shown to modify covalently rHetR. Dansyl f luoride (DnsF), another serine-type pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 29 publications
4
102
0
Order By: Relevance
“…Our results are consistent with recent data indicating that HetR is likely to be the PatS receptor (15). HetR is a key activator of heterocyst development (5) that was previously shown to be positively autoregulated (2) and to have autoproteolytic activity (38). Zhao's laboratory has now shown that HetR forms a homodimer with DNA-binding activity and that this DNA-binding activity is inhibited in vitro by synthetic PatS pentapeptide (15).…”
supporting
confidence: 82%
“…Our results are consistent with recent data indicating that HetR is likely to be the PatS receptor (15). HetR is a key activator of heterocyst development (5) that was previously shown to be positively autoregulated (2) and to have autoproteolytic activity (38). Zhao's laboratory has now shown that HetR forms a homodimer with DNA-binding activity and that this DNA-binding activity is inhibited in vitro by synthetic PatS pentapeptide (15).…”
supporting
confidence: 82%
“…The gel was stained using a silver-staining kit (Bio-Rad, Hercules, CA). To determine the pI of the Pa-AMP-1, isoelectric focusing gel electrophoresis was performed according to the method of Zhou et al (1998). The gel was stained with Coomassie Brilliant Blue.…”
Section: Electrophoresismentioning
confidence: 99%
“…The antibodies were specific to Pa-AMP-1 and GFP. Immunoblotting after Tricine SDS-PAGE was performed using horseradish peroxidase-conjugated goat anti-rabbit IgG antibodies as secondary antibodies, as described in Zhou et al (1998). To detect Pa-AMP-1 secretion from the pokeweed seeds during germination, seeds were first incubated in water for 12 h at 28°C, and then transferred onto a PVDF membrane, which was wet first before being placed on top of four layers of Whatman filter paper in a Petri dish.…”
Section: Immunological Detection Of Pa-amp-1mentioning
confidence: 99%
“…NtcA is required for development and function of mature heterocysts, and for the expression of nitrogen transport and assimilation systems as well as N 2 fixation (Herrero et al, 2001). HetR is a key regulator of heterocyst differentiation (Buikema & Haselkorn, 1991) and is an autoregulated serine-type protease that can degrade itself and possibly other proteins (Zhou et al, 1998). HetR shows enhanced induction within 1-2 h of nitrogen stepdown, and within 3?5 h hetR expression is clearly localized to spaced cells, presumably developing pro-heterocysts (Black et al, 1993).…”
Section: Introductionmentioning
confidence: 99%